Інституційна система сталого розвитку аграрного сектора: механізм адаптації в умовах флуктуацій - Kyfyak, Viktoria; Дубінський, Роман (Сталий розвиток економіки, 2024)
Анотація. Стаття присвячена дослідженню інституційної системи сталого розвитку в аграрному секторі та механізмам адаптації до флуктуаційних умов. Проаналізовано функціональне призначення основних ін-ституційних елементів, які визначають сталість розвитку аграрної сфери, включаючи правові, економічні та соціокультурні фактори. Визначено характеристики механізмів адаптації, які дозволяють аграрному сектору ефективно функціонувати в умовах флуктуацій військових дій, ринкових умов, кліматичних змін та інших нестабільних факторів. Охарактеризовано ключові аспекти, які сприяють успішній адаптації, такі як гнуч-кість виробництва, інноваційні підходи, соціальна взаємодія та ефективне використання ресурсів. Надано практичні рекомендації щодо вдосконалення інституційної системи сталого розвитку аграрного сектору че-рез формування інституційних угод.
INSTITUTIONAL SYSTEM OF SUSTAINABLE DEVELOPMENT OF THE AGRICULTURAL SECTOR: MECHANISM OF ADAPTATION IN CONDITIONS OF FLUCTUATIONS
Summary. The relevance of the research lies in the need to adapt existing institutional mechanisms to new realities. Changes in fluctuating conditions necessitate not only reactive measures but also systemic innovations aimed at establishing a more effective and stable institutional foundation for the sustainable development of the agricultural sector. The research aims to identify new challenges arising due to changes amidst fluctuations and develop recom-mendations to enhance the agricultural sector's sustainability. The article is devoted to the study of the institutional system of sustainable development in the agricultural sector and the mechanisms for adapting to fluctuating condi-tions. The institutional system, considered as a dynamic organism, capable of responding and adapting to fluctua-tions, contributes not only to maintaining the sustainable development of the agricultural sector, but also actively influences its innovative and effective development in the conditions of change. The functional purpose of the main institutional elements that determine the sustainability of the development of the agrarian sphere, including legal, economic and socio-cultural factors, is analyzed. The characteristics of the adaptation mechanisms that allow the agricultural sector to function effectively in the conditions of fluctuations of military operations, market conditions, climatic changes and other unstable factors are determined. Key aspects that contribute to successful adaptation are characterized, such as production flexibility, innovative approaches, social interaction and efficient use of resources. Practical recommendations are provided for improving the institutional system of sustainable development in the agricultural sector through the institutional agreement formation. It was concluded that solving new challenges in the field of sustainable development in the agricultural sector requires joint efforts of the government, business, and the scientific community, whose efforts should be integrated through institutional agreements to ensure the sustainable development of the agricultural sector in conditions of instability and fluctuations. Keywords: institutional system, sustainable development, agricultural sector, fluctuations, adaptation mechanism, institutional agreement.
Keywords: Ключові слова: інституційна система, сталий розвиток, аграрний сектор, флуктуації, механізм адаптації, інституційна угода